ULTRASOUND CRITERIA FOR DIABETIC FETOPATHY IN FETAL MACROSOMIA FROM MOTHERS WITHOUT DIABETES MELLITUS - Baevа, Irina Yuryevna; Konstantinova, Olga Dmitrievna (Mother and Baby in Kuzbass, 2026)
The aim of the research – the frequency detection of diagnostic value of antenatal ultrasound signs of diabetic fetopathy in the case of fetal macrosomia at different stages of pregnancy by mothers without diabetes mellitus.Material and methods. The object of the prospective cohort study were 300 pregnant women with a large fetus of 4000 g or more (main group) and 200 pregnant women with a fetus with an average body weight of 3000-3999 g (control group), as well as their newborns, whose observation and study were carried out in the period from January 1, 2015 to January 1, 2021.Results. The analysis of diabetic fetopathy markers of large fetuses revealed a significantly higher incidence in the case of asymmetric fetal development. The buccal coefficient for fetal macrosomia had the highest sensitivity and specificity. Cardiomegaly of large fetuses was significantly more common with asymmetric fetal development beginning in the third trimester of pregnancy and had low sensitivity (up to 56%) and specificity (up to 86%) for diagnosing diabetic fetopathy by large fetuses. Hepatomegaly had low sensitivity and specificity for diagnosing diabetic fetopathy. The adrenal coefficient for fetal macrosomia had high specificity (80%) and low sensitivity (38%) for diagnosing diabetic fetopathy.Conclusion. The asymmetric form of macrosomia itself is one of the main markers of the development of diabetic fetopathy, which emphasizes the importance of determining the type of development of a large fetus.
Keywords: macrosomia; ultrasound scan; diabetic fetopathy; diagnosis of macrosomia